Fruit processing (Blackie Academic and Professional, 1996)
This book provides a concise, thorough and authoritative coverage of the technology of fruit processing from a world wide perspective. Detailed coverage of the manufacture of fruit by-products, environmental issues and water quality reflect the importance of these topics